2007
DOI: 10.1111/j.1523-5378.2007.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Degree and Duration of Acid Suppression are Related to Helicobacter pylori Eradication by Triple Therapy

Abstract: The sustained intragastric pH > 4.0 for a longer postdose time appears to be required for a successful eradication of H. pylori with lansoprazole and acid-labile antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(155 citation statements)
references
References 32 publications
6
146
0
3
Order By: Relevance
“…In this study, advanced age showed a trend toward a higher eradication rate, and a large French study reported advanced age as a significant factor for successful eradication [14] . Gastric pH elevation increases the rate of successful eradication [15] . Although it has been reported that integrated acidity in the general population is not affected by age [16] , acidity in the elderly may be more suppressed by PPI than in younger people.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, advanced age showed a trend toward a higher eradication rate, and a large French study reported advanced age as a significant factor for successful eradication [14] . Gastric pH elevation increases the rate of successful eradication [15] . Although it has been reported that integrated acidity in the general population is not affected by age [16] , acidity in the elderly may be more suppressed by PPI than in younger people.…”
Section: Discussionmentioning
confidence: 99%
“…With this eradication therapy, gastric pH rises due to the effects of the PPI and is maintained in the neutral range, allowing the antimicrobial agents to display good antimicrobial activity. Achieving sufficient gastric acid secretion-inhibiting effects is important, and a correlation is thought to exist between gastric pH and the success of H. pylori eradication therapy (14). RPZ is known to increase gastric pH to between 6 and 8 more rapidly and reliably than other PPIs and to effectively inhibit nocturnal secretion of gastric acid (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of esomeprazole (EPZ) and RPZ were less affected by the CYP2C19 polymorphism, Open Journal of Gastroenterology The main role of gastric acid-inhibitory agents in H. pylori eradication therapy is to increase the bioavailability and stability of antibacterial agents in the stomach [34]. In patients who achieved successful eradication with LPZ therapy, the median 24-hour pH was 6.4 (range 5.0 -7.6), which was higher than that in patients without eradication (pH 5.2, 2.2 -6.2), and the median percentage time of a pH < 4.0 during the 24-hour post-dose period in patients with eradication (0.5%) was significantly shorter than that in patients without eradication (26.7%) [35]. AMPC has poor stability, particularly at a low pH, but nevertheless has a half-life of over 15 hours at pH 2.…”
Section: Discussionmentioning
confidence: 69%